Avaliação da aprendizagem por meio de instrumentos com foco na atividade da sala de aula - Silva, Expedito Pereira da (2016)
This master’s final work has as its objective to investigate the way in which the teacher evaluates student’s apprenticeship in basic education, by the usage of evaluation instruments, having as its main focus the classroom activities, and is inserted in the research Field: “Evaluation and Pedagogical Action” from the postgraduation programme in Education: “Former’s formation” – Field: Former’s formation, from PUC-SP. Its start point are experiences lived by the author of the present study, emphasizing the period in which he undertook scholar management, specifically occupying the principal position of a state public school. The present research had a qualitative approach, characterized by the analysis carried out through collected data by four elementary school teachers, detailing the real condition related to the analyzed situations, giving sense to the statements, interpreting and significations, always with a look directed to the efficiency of evaluation instruments. The results of this research have shown that teachers reflect upon their own formation; recognize the conceptual vulnerabilities regarding knowledge about apprenticeship evaluation, especially the evaluation instruments and the collected data interpretation. Inasmuch as the collaborator teachers were acquiring comprehension over the topic, they were also reassessing their techniques. By the means of training actions, the central point of teachers’ reflections is to recognize that from the relationship between school and university knowledge, focused on our course, former’s formation, it is noticed that the training and continuous formation can favor professional evolution. We also believe that evaluating and knowing the instruments can even contribute to the school conception changing and to our evaluation practices as teachers, aiming to transform these. Comprehending how teachers succeeded in enabling the implementation process of an evaluative culture and the success in the achieved results can also represent a contribution of this work to school teachers. Seeking theoretical basis, we used the authors Despresbiteris & Tavares (2009); Luckesi (2010). To sum up, we will introduce the research data and its analysis